The expressiveness of perceptual experience : physiognomy reconsidered - Lindauer, Martin S. (Consciousness & emotion book series ;, 2013)
A face strikes us immediately as sad, and so, too, do a mourner, a willow tree, a house on a prairie, and a group of onlookers. The spontaneous emergence of affective and other qualities of people, things, places, and events falls under the heading of physiognomy, a phenomenon discussed since at least Aristotle, and a key feature of evolutionary theory, psychology, and perception as well as professional practice ("profiling") and popular talk. However, physiognomy is a controversial topic because of a suspect history, and is often renamed as non-verbal communication. The Expressiveness.